Entrepreneurship Education and Locus of Control: Their Influence on Students' Entrepreneurship Interest - Achmad Zainul Rozikin; Endang Sri Suyati (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2023)
Abstract A person's interest in entrepreneurship can be influenced by internal factors and external factors. Internal factors include locus of control, while external factors include entrepreneurship education. The purpose of this study was to determine how much influence locus of control and entrepreneurship education had on students' interest in entrepreneurship. The data for the three variables (entrepreneurship education, locus of control, and interest in entrepreneurship) were obtained by distributing questionnaires to the students. The population of this study was 287 students, while the sample was 167 students. The sampling technique used was random sampling technique. The results of this study indicate that interest in entrepreneurship can be influenced by entrepreneurship education and locus of control partially or simultaneously, although the contribution of locus of control is greater than entrepreneurship education.Keywords:Entrepreneurship, Interest In Entrepreneurship, Locus Of Control, Entrepreneurship Education